THE EFFECTIVENESS OF HOLISTIC CARE-BASED HEALTH EDUCATION PREVENTS EARLY TEENAGE MARRIAGE AT ISLAMIC SENIOR HIGH SCHOOL 4 BAOURNE BOJONEGORO - Wiwik Muhidayati; Titik Nuryanti; NUR AZIZAH; agus ari afandi; yuli Admasari (Indonesian Midwifery and Health Sciences Journal)
Background: Teenage are in the age range between 10-19 years. Meanwhile, teenage is a period of transitional development from childhood to adulthood so that it will influence holistic changes both biologically, psychologically, socially and spiritually. Early marriages (<19 tahun) should not be carried out considering the many risks that may occur to the mother and baby. Therefore, it is important to know the influence of holistic care-based health education on efforts to prevent early teenage marriage. Method:  The design of this research is quasi-experimental with a pre-posttest control group design. The population in the study was all MAN 4 Baureno school student totaling 313 respondents. The sample was 37 respondents using a non-probability method using purposive sampling technique. Data was collected using a questionnaire and the Wilcoxon Sign Ranks Test was carried out with a significance level of 0.05.Result: The results of the Wilcoxon Signed Ranks Test showed a value of p = 0.000 (p<0.05) meaning that there was a significant difference in the level of knowledge and after holistic care education was carried out. Conclusion : Holistic care-based education can increase knowledge. Holistic care-based education seen from a biological, psychological, social and spiritual perspective is very suitable for health education, health services and health development that is suitable for adolescent children.